PENGARUH PENGETAHUAN GIZI KELUARGA TERHADAP POLA MAKAN SISWA DI SMK N 6 YOGYAKARTA - nurul faizah (Universitas Sarjanawiyata Tamansiswa, 2023)
This study aims to find out: 1) the family nutrition knowledge of Class X students in the Culinary Department, 2) the family eating patterns of Class X students in the Culinary Department, 3) the effect of family nutrition knowledge on the eating patterns of class X students majoring in culinary at SMK Negeri 6 Yogyakarta Academic Year 2021/2022. This research includes descriptive research with a quantitative approach. Total population of 144 students. The sampling technique used the slovin formula with a significant level of 10%, obtaining 59 students. Data analysis techniques used descriptive analysis and hypothesis testing using the product moment correlation test which was preceded by a prerequisite analysis test. The results showed that: 1) family nutrition knowledge of class X students majoring in culinary was in the sufficient category by 29 respondents (49,2%), 2) the eating patterns of class X students majoring in culinary were in the sufficient category by 23 respondents (39,0%), 3) there is a positive and significant influence between family nutritional knowledge on students' eating patterns with rcount > rtable of 0.463 > 0.252 and R2 = 21.4%. keyword: knowledge, nutrition, dietary habit.